From Imagination to Compassion and Democracy: Martha Nussbaum on the Role of Art - Ferdinand Indrajaya (IJCAS (International Journal of Creative and Arts Studies), 2019)
ABSTRACTIt is undeniable that most of our modern universities are portraying themselves as factory-like institutions which manufacture useful knowledge. The term “useful knowledge” refers to a type of knowledge which directly has immediate payoff and practically commodifiable. Most modern universities are no longer spotlighted as the generator of new knowledge, the influential bodies in civic life and nation-state, the greatest critics of public policies, but reduced to and figuring as a major agent of economic growth. Posting economic growth as the model for universities is a form of corporatism in higher education level. Art disciplines, as a part of humanities, are inevitably framed by such a model. In which, art is understood as a mere aesthetic commodity and the artist is seen as a mechanical subject to be manipulated by profit motifs. This view has been well prevailing, but it is not incontestable. This paper is written as an attempt to critically respond towards such prevailing corporatist view. To do that, the author borrows some philosophical perspectives from an American philosopher, Martha C. Nussbaum (1947–now). Her philosophical accounts on art, imagination, and compassion as a form of distinctive moral emotion are considerably an adversary to the current perspective of art education which has been colonized by corporatism. From her perspective, more than just a mere commodity, art has a significant role in upholding democracy. Art has the power to nurture compassion, in which respect and concern for others are inherent. Respect and concern are the vital-ethical ingredients for democracy. One particular art form which, according to Nussbaum, can nurture compassion, intensively, is a tragedy. Through which, we shall see other people as human beings, not as objects of manipulation. Such philosophical views of hers may re-attune our current perspective on art education. ABSTRAK Sulit dipungkiri bahwa kebanyakan dari universitas modern/masa kini kerap menampilkan wajahnya sebagai institusi yang serupa dengan pabrik manufaktur pengetahuan yang berguna. Istilah “pengetahuan yang berguna” merujuk kepada pengetahuan yang berdampak langsung dan secara praktis dapat dikomodifikasi. Kebanyakan dari universitas masa kini tidak lagi disorot sebagai sebuah generator bagi kebaruan pengetahuan, lembaga yang berpengaruh bagi kehidupan civic dan negara bangsa, kritikus terbesar bagi kebijakan-kebijakan publik, akan tetapi terreduksi sebagai agen utama dari pertumbuhan ekonomi. Penempatan pertumbuhan ekonomi sebagai model yang diacu oleh universitas sesungguhnya adalah sebuah wujud korporatisme pada aras perguruan tinggi. Disiplin keilimuan seni, sebagai sebuah bagian dari humaniora, turut terbingkai oleh model tersebut. Dari perspektif korporatisme, seni dipahami sekadar komoditas estetis dan sang seniman dipandang sebagai subjek mekanistik yang dapat dimanipulasi oleh motif-motif profit. Pandangan ini masih bertahan dan populer sampai saat ini, akan tetapi tidak berarti tidak dapat dikontestasikan. Makalah ini ditulis sebagai sebuah upaya untuk menanggapi secara kritis pandangan korporatistik tersebut. Dalam rangka mencapai tujuan tersebut, penulis merujuk kepada beberapa pandangan filosofis dari salah satu filosof asal Amerika, yakni Martha Nussbaum (1947-sekarang). Pandangan filosofisnya tentang seni, imajinasi, dan bela rasa sebagai sebuah bentuk emosi moral distingtif adalah lawan dari perspektif tentang pendidikan seni yang telah dikolonisasi oleh korporatisme. Seni, melalui perspektifnya, memiliki peran yang signifikan dalam menegakkan demokrasi; keberadaannya lebih dari sekadar komoditas. Baginya seni berdaya untuk memelihara bela rasa, yang di dalamnya rasa hormat dan kepedulian terhadap yang lain inheren. Rasa hormat dan kepedulian, dalam hal ini, adalah unsur etis yang vital bagi demokrasi. Salah satu bentuk partikular dari seni yang menurut Nussbaum mampu secara intensif memelihara bela rasa, adalah tragedi. Melalui tragedi, kita akan memandang orang lain sebagai manusia, bukan sebagai objek untuk dimanipulasi. Pandangan-pandangan filosofis darinya merupakan ajakan bagi kita untuk menala kembali perspektif yang bertahan hingga kini tentang pendidikan seni.